Perspectives on AI Education: the Importance of Including AI Skills and Technical Competencies in Curricula - Bustillos Ortega, Olda (2024)
Artificial intelligence (AI) is the most important invention of humanity and we have it present in society and the economy, but it is also now impacting the academy where teachers and students make use of linguistic and interaction models such as ChatGPT and others. This study refers to surveys and research on the use and applications of AI. The results of a survey on AI training topics are shown, which was applied to teachers and university students in Costa Rica. A comparative analysis of the results is made and tables of both groups surveyed are presented. Additionally, basic guidelines are provided to formulate AI content and syllabus within the curriculum of a technology career. Finally, recommendations are given on the technical skills and competencies to be developed.